The assessment of Mungbean seed yield and quality changes in response to environmental factors in different planting dates - Seyede Sakineh Hoseini; Farshid Ghaderi-Far; Afshin Soltani; Yunes Mohamad-Nejad; Morteza Gorzin (پژوهش‌های حبوبات ایران)
Introduction Planting date is one of the important issues in agronomy that could be changing quantitative and qualitative characteristics of crop seeds. Planting date changes seed quality by providing different environmental conditions such as temperature, relative humidity, day length, radiation, and incidence of pathogens. It is also effective on seed yield. It affects duration of growth and development. A suitable planting date leads to optimal utilization of climatic conditions such as temperature, humidity, day length. It is also important for flowering and grain filling period to take place at the same time with favorite environmental conditions. As a result, it can improve seed yield and seed quality. Some factors such as high temperatures, frequent wetting and drying of air, high relative humidity, and continuous rainfalls have a significant negative effects on seed quality. These conditions during seed development reduce seed quality in the field. It is obvious that such conditions can be occurred on both early and late planting dates. Thus, according to an important role of planting date in determination of seed yield and quality, in this study the effects of environmental conditions during seed filling period on seed yield and quality of mungbean (Vigna radiata L.) were evaluated by implementing different planting dates in field conditions.